INTERNAL CONTROL SYSTEM ANALYSIS ON ACCOUNT RECEIVABLES IN E-RN TRADING BUSINESS - Nicholas Renaldo; Sudarno Sudarno; Marice Br. Hutahuruk; Suyono Suyono; Suhardjo Suhardjo (STIE Binaniaga, 2021)
Large bad debt will disrupt cash flow in the business. This study aims to determine how the implementation of COSO-based internal control in the E-RN Trading Business. This research was conducted in Pekanbaru City, Riau. The data used in this study are primary data and secondary data. Collecting data using observation techniques, interviews, literature studies, and questionnaires. The research method uses descriptive analysis, binomial test, and sign test. The test results show that the control environment, risk assessment, and supervision and monitoring have not been effective in the E-RN Trading Business, but control activities and information and communication have been running effectively in the E-RN Trading Business. Overall testing shows that the implementation of the E-RN Trading Business internal control system is still less effective. Recommendations for E-RN Trading Business implements policies to limit and monitor employee actions so as not to deviate, comply with existing regulations and policies, and improve employee performance, conducts an analysis beforehand and pays attention to receivables, regularly holds meetings after a problem is discovered, and conducts unannounced checks once a week so that fraud does not occur.